BAMBATHA AT MPANZA: THE MAKING OF A REBEL - Monama, Fankie (Scientia Militaria - South African Journal of Military Studies, 2012)
Bambatha is widely known as the chief who led a group of men to confront the Natal colonial government in protest against poll tax. He lived in a broken, sandy and stoney area known as Mpanza valley, to the north of Greytown, in the Natal colony of the former British Empire. The inhabitants of this valley were the Zulu tribe called Amazondi (officially called Abasengome). This land was dry and poor for cultivation and for game. It was a farmland owned by white men but settled by the Amazondi since 1854 as a “private location” of indigenous people who did not live in an officially designated Native Location (an exclusive site for the settlement of indigenous people). The white people were called the thorns. Bambatha led the last armed resistance of the Africans before the establishment of the Union of South Africa in 1910. He was eventually captured and beheaded. He provided the source of strength to boost the morale of those who continued with the struggle for liberation in subsequent years. This is the perception around Bambatha and his rebellion in 1906. But how exactly did it happen that he became a defiant chief who did not acquiesce to the demands of the colonial government? This book provides a descriptive analysis of the career of Bambatha until his flight to Zululand after the failure of his endeavour-armed resistance.